Polybutylene terephthalate compositions for high frequency radio wave applications

By melting and mixing polybutylene terephthalate with hollow glass bubbles and other additives to form a polymer composition suitable for high-frequency radio wave applications, the problems of high cost and insufficient performance of existing materials are solved, and the problem of The effects of low dielectric constant, low dissipation factor and high metal adhesion strength are suitable for 5G and higher frequency applications.

CN119213074APending Publication Date: 2024-12-27SABIC GLOBAL TECHNOLOGIES BV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380040803.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-27
Filing Date
2023-05-25
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing high-frequency radio wave application materials are costly, heavy weight, high dielectric constant and dissipation factor values, and insufficient mechanical and thermal performance, making it difficult to meet the needs of 5G and higher frequency applications.

Method used

The mixture of polybutylene terephthalate (PBT) and hollow glass bubbles and other additives is used to modify it through melt mixing to form a low dielectric constant, low dissipation factor, high metal adhesion strength, low thermal expansion coefficient, Polymer compositions with good mechanical strength, suitable for radio wave applications with frequencies of 6 GHz or higher.

Benefits of technology

It realizes high-frequency materials with low cost, light weight and superior performance, and is suitable for radio wave applications with 5G and higher frequencies, meeting the mechanical and thermal performance requirements of high-frequency equipment.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

A polybutylene terephthalate composition for use in 6 GHz or higher frequency radio wave applications includes a mixture of polybutylene terephthalate and hollow glass bubbles having an average diameter or particle size of 5 [mu] m to 80 [mu] m. The polybutylene terephthalate composition further includes at least one of glass fibers having a length of 0.5 to 10 mm, a width or diameter of 5 to 15 [mu] m, alumina fibers having a length of 1 to 5 mm, a width or diameter of 1 to 30 [mu] m, a cycloolefin copolymer, and a polycarbonate. The polybutylene terephthalate composition is prepared by melt mixing polybutylene terephthalate with various materials to modify polybutylene terephthalate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to polybutylene terephthalate compositions useful for high frequency radio wave applications. Background Art

[0002] The emergence of 5G communication technology and related equipment has prompted the need for polymer materials with low cost, light weight, low dielectric constant (Dk) and dissipation factor (Df) values, high metal adhesion strength, low coefficient of thermal expansion (CTE), and good mechanical and thermal properties. Currently, FR-4 glass reinforced epoxy resin laminates are widely used as antenna substrates for frequency applications below 6 GHz. Due to the high Dk value (>4) and Df value (>0.01) of FR-4 laminates, they are not suitable for high-frequency (i.e. >6 GHz) applications.

[0003] On the other hand, materials such as polytetrafluoroethylene (PTFE), liquid crystal polymer (LCP), and modified polyimide (M-PI) are considered suitable materials for higher frequency (>6GHz) antennas and other niche applications due to their low Dk and Df values. However, these materials are very expensive and do not meet the lightweight standards required for the target applications. In addition, each material faces other specific challenges. In particular, the use of PTFE brings some challenges such as higher system cost (including material and processing costs), poor metal adhesion, high CTE along the Z axis, and high density.

[0004] In this regard, other commercially available polymer materials, such as polybutylene terephthalate (PBT), can be selected because PBT has lower Dk (about 3 at 10 GHz) and Df (about 0.005 at 10 GHz) than FR-4, and has better metal adhesion properties than PTFE. However, the mechanical and thermal properties of pure PBT are not sufficient to meet certain manufacturing process steps and operating conditions, such as surface mount technology (SMT) processes. Although the addition of certain additives to PBT can improve its mechanical and thermal properties, these additives may affect the dielectric properties and metal adhesion characteristics of PBT.

[0005] Therefore, it is necessary to modify PBT with additives that can provide synergistic effects so that the modified PBT has low Dk and Df values, high metal adhesion strength, low CTE, and good mechanical and thermal properties, so as to be suitable for higher frequency (i.e., greater than 6 GHz) applications. Summary of the invention

[0006] The polybutylene terephthalate (PBT) composition for 6 GHz or higher frequency radio wave applications is composed of a mixture of polybutylene terephthalate, hollow glass bubbles with an average diameter of 5 to 80 microns, and at least one of several additives. The additives may include glass fibers with a length of 0.5 to 10 mm and a width or diameter of 5 to 15 microns, alumina fibers with a length of 1 to 5 mm and a width or diameter of 1 to 30 microns, polyethylene terephthalate, and / or polycarbonate.

[0007] The PBT composition may include hollow glass bubbles in an amount of 1 wt % to 35 wt %. The hollow glass bubbles may have at least one of a crushing strength of 30 MPa or more, a true density of 0.3 g / cc to 0.8 g / cc, and a gas volume of 50% to 90%.

[0008] The PBT composition may include glass fibers in an amount of 40 wt% or less of the total weight of the composition. The glass fibers have a dielectric constant (Dk) of 6 or less as measured at 6 MHz or more according to ASTM D150; a dissipation factor (Df) of 0.005 or less as measured at 6 MHz or more according to ASTM D150; and a coefficient of thermal expansion (CTE) of 35 x 10 -6 / ℃ or lower.

[0009] The PBT composition may further include alumina fibers in an amount of 40 wt % or less based on the total weight of the composition.

[0010] The PBT may be a low intrinsic viscosity (IV) resin (IV value of 1.4 dl / g or less) or a high intrinsic viscosity (IV) resin (IV value of 1.5 dl / g or more) or a mixture of such resins.

[0011] The PBT composition may also include polycarbonate (accounting for 30% or less of the total weight of the composition) and polyethylene terephthalate (accounting for 30% or less of the total weight of the composition).

[0012] The PBT composition may also include at least one of a stabilizer, a coupling agent, a nucleating agent, a thermal conductor, a flame retardant additive, a thermal conductive additive, a binder, an antiblocking agent, an antistatic agent, an antioxidant, a neutralizer, an acid scavenger, a foaming agent, a crystallization aid, a dye, a flame retardant, a filler, a hard filler, a soft filler, an impact modifier, a mold release agent, an oil, another polymer, a pigment, a treating agent, a reinforcing agent, a light stabilizer, an anti-UV agent, a slip agent, a flow modifier, and combinations thereof.

[0013] The PBT composition has a Dk value of 2.5 or less, a Df value of 0.005 or less, and a metal adhesion peel strength of 0.1 N / mm or more, as measured according to ASTM B533 or IPC-TM-650; a coefficient of thermal expansion (CTE) of 35 ppm / °C or less, as measured according to ASTM D696; a heat deformation temperature (HDT) of 200°C or more, as measured according to ASTM D648; a water absorption of 0.05 wt% or less, as measured according to ASTM D570; a tensile modulus of 2000 MPa or more, as measured according to ASTM D638; a tensile strength of 35 MPa or more, as measured according to ASTM D638; a density of 1.4 g / cc or less; a UL94 flame retardant rating of V0@1.5 mm; and a thermal conductivity of 0.3 W / mK or less, as measured according to ASTM C518.

[0014] The PBT composition is made into an article of manufacture. The article of manufacture may be a telecommunications device or component, a high frequency (greater than 6 GHz) electrical device, a high frequency (greater than 6 GHz) multi-generation telecommunications device or component, a 5G or higher generation telecommunications device or component, a telecommunications device housing, a radar cover, a radio frequency (RF) filter, an RF connector, an EMI shield, an antenna substrate, a waveguide substrate or carrier, an antenna substrate in a base station antenna, or an automotive radar component.

[0015] In a method of forming a PBT composition for 6 GHz or higher frequency radio wave applications, polybutylene terephthalate is modified by melt mixing polybutylene terephthalate with a hollow glass bubble material having an average diameter of 5 to 80 microns and at least one of several additives dispersed throughout the polybutylene terephthalate. These additives may include glass fibers having a length of 0.5 to 10 mm and a width or diameter of 5 to 15 microns, alumina fibers having a length of 1 to 5 mm and a width or diameter of 1 to 30 microns, and polycarbonate, thereby making these materials. DETAILED DESCRIPTION

[0016] Polybutylene terephthalate (PBT) is a readily available and relatively low cost material compared to the high cost materials currently used for high frequency radio wave applications. However, PBT has not been widely used for high frequency radio wave applications due to its inherent deficiencies at these higher frequencies. In the present invention, PBT is melt mixed with a synergistic additive mixture to overcome these shortcomings and make the PBT composition suitable for radio wave applications at 6 GHz or higher frequencies.

[0017] Modified PBT is modified to have low weight, low dielectric constant (Dk), low dissipation factor (Df), high metal adhesion strength, low coefficient of thermal expansion (CTE), high mechanical strength, and good thermal properties. These properties can be achieved by using a mixture of PBT with specific additives described in this article.

[0018] In the co-application and co-pending patent application entitled "Polypropylene Composition for High Frequency Radio Wave Applications" (attorney case number: 21T&I0030), a modified polypropylene (PP) for 6GHz or higher frequency radio wave 5G applications is disclosed. Although such modified polypropylene is useful in many such applications, due to the low melting point of polypropylene (about 160°C), it has limitations relative to those processing conditions and operations that occur at much higher temperatures (such as during soldering for surface mount technology (SMT) applications). In contrast, PBT has a much higher melting point (about 220°C) and can therefore be used in higher temperature applications such as SMT.

[0019] The PBT component in the polymer mixture can constitute a homopolymer of polybutylene terephthalate resin. These homopolymers can be formed by polycondensation of a dicarboxylic acid containing terephthalic acid or its ester-forming derivatives (such as C1 to C6 alkyl esters or acid halides, etc.) and an ethylene glycol component containing an alkylene glycol containing at least four carbon atoms (such as 1,4-butanediol) or its ester-forming derivatives.

[0020] Examples of suitable commercially available PBT homopolymers are VALOX manufactured by SABIC of the United States or SABIC of Europe. TM Resin 176 or VALOX TM Resin 3007.

[0021] In other embodiments, the PBT component may include a copolymer of PBT polyethylene glycol (PBT-PET multi-block copolymer), PBT-polyethylene oxide terephthalate (PBT-PEOT block copolymer), PBT-cyclobutene dioleate (PBT-DLA copolymer), and a random PBT-PET copolymer (wherein the binary compound component may be selected from the group consisting of ethylene glycol, propylene glycol, polybutene-1,4-cyclohexane dicarboxylate (PBCD), polybutene-1,3-cyclopentane dicarboxylate (PBCP), and polybutene-polylactic acid copolymer). When such copolymers are used, the content of non-butylene terephthalate copolymer units in the PBT copolymer may be 30 wt% or less, and in many cases 5 wt% to 30 wt% may be used. In a specific embodiment, the content of non-butylene terephthalate copolymer units in the PBT copolymer can be at least 0.1 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.8 wt%, 0.9 wt%, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, 15 wt%, 16 wt%, 17 wt%, 18 wt%, 19 wt%, 20 wt%, 21 wt%, 22 wt%, 23 wt%, 24 wt%, 25 wt%, 26 wt%, 27 wt%, 29 wt% and 30 wt%.

[0022] In certain embodiments, the polybutylene terephthalate composition is substantially free of polytetrafluoroethylene (PTFE). As used herein, the term "substantially free" means that a component of the composition is not actively or intentionally added to the composition, but may be present as an impurity at a level less than about 0.01% by weight of the composition.

[0023] It should be noted in the description that if a value, concentration or range is given, each value should be modified once by the word "about" (unless it is clearly modified) and then be considered unmodified unless the context indicates otherwise. In addition, in the description, it should be understood that the purpose of listing or describing a useful, suitable or similar range of quantities is to treat any and every value within the range, including the endpoints, as having been described. For example, "a range from 1 to 10" should be understood to mean every possible number on the continuum between about 1 and about 10. Therefore, even if a specific point within the range is explicitly indicated or mentioned, or even if no point within the range is mentioned, it should be understood that the inventor understands and understands that any and all points within the range should be considered as indicated, and the inventor owns the entire range and all points within the range, including smaller ranges within larger ranges.

[0024] As discussed throughout the following specification, as it relates to the PBT component of a PBT composition, the expression "PBT" is intended to include both PBT homopolymers and PBT copolymers unless otherwise expressly stated or apparent from its context.

[0025] The PBT component of the composition can be characterized by various properties, such as average molecular weight, density, intrinsic viscosity, melt flow index (MFI), polydispersity index (PDI), tensile strength at yield, tensile modulus, tensile elongation at yield, notched Izod impact strength, hardness, or combinations thereof.

[0026] The average molecular weight (Mw) of the PBT component can be 30,000 to 200,000 as measured by high temperature gel permeation chromatography. In particular, the average molecular weight (Mw) of the PBT can be at least, equal to, and / or between any two of the following values, as measured by high temperature (40-50° C.) gel permeation chromatography using 1,1,1,3,3,3-hexafluoroisopropanol (HFIP as solvent): 30,000, 40,000, 50,000, 60,000, 70,000, 80,000, 90,000, 100,000, 110,000, 120,000, 130,000, 140,000, 150,000, 160,000, 170,000, 180,000, 190,000, and 200,000. Unless otherwise stated, all average molecular weights (Mw) of polymers described herein are determined by high temperature gel permeation chromatography.

[0027] The density of PBT can be 1.3g / cm 3 or 1.4 g / cm 3 In particular, the density of PBT may be at least the following, equal to the following and / or between any two of the following values: 1.30 g / cm 3 , 1.31g / cm 3 , 1.32g / cm 3 , 1.33g / cm 3 , 1.34g / cm 3 , 1.35g / cm 3 , 1.36g / cm 3 , 1.37g / cm 3 , 1.38g / cm 3 , 1.39g / cm 3 and 1.40g / cm 3 .

[0028] The PBT may be a low intrinsic viscosity (IV) resin having an IV of 1.4 dl / g or less or a high IV resin having an IV of 1.5 dl / g or more or a mixture of such PBT resins. The intrinsic viscosity of the PBT is measured in dilute solution using a capillary viscometer according to the ISO-1628-5 protocol. In certain embodiments, the low IV PBT may have an IV of at least, equal to, and / or between any two of the following: 0.2 dl / g, 0.3 dl / g, 0.4 dl / g, 0.5 dl / g, 0.6 dl / g, 0.7 dl / g, 0.8 dl / g, 0.9 dl / g, 1.0 dl / g, 1.1 dl / g, 1.2 dl / g, 1.3 dl / g, and 1.4 dl / g. In certain embodiments, the high IV PBT resin may have an IV of at least, equal to, and / or between any two of 1.5 dl / g, 1.6 dl / g, 1.7 dl / g, 1.8 dl / g, 1.9 dl / g, 2.0 dl / g, 2.1 dl / g, 2.2 dl / g, 2.3 dl / g, 2.4 dl / g, and 2.5 dl / g.

[0029] When such a mixture of low IV and high IV PBT resins is used, the low IV PBT resin is used in an amount of 0.1 wt% to 99.9 wt% based on the total weight of the low IV and high IV PBT resins. When a mixture of low IV and high IV PBT resins is used, the low IV resin may be used in an amount of at least, equal to, and / or between any two of the following: 0.1 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.8 wt%, 0.9 wt%, 1.0 wt%, 1.1 wt%, 1.2 wt%, 1.3 wt%, 1.4 wt%, 1.5 wt%, 1.6 wt%, 1.7 wt%, 1.8 wt%, 1.9 wt%, 2.0 wt%, 2.1 wt%, 2.2 wt%, 2.3 wt%, 2.4 wt%, 2.5 wt%, 2.6 wt%, 2.7 wt%, 2.8 wt%, 2.9 wt%, 3.0 wt%, 3.1 wt%, 3.2 wt%, 3.3 wt%, 3.4 wt%, 3.5 wt%, 3.6 wt%, 3.7 wt%, 3.8 wt%, 3.9 wt%, 4.0 wt%, 4.1 wt%, 4.2 wt%, 4.3 wt%, 4.4 wt%, 4.5 wt%, 4.6 wt%, 4.7 wt%, 4.8 wt%, 4.9 wt%, 5.1 wt%, 5. 6wt%, 2.7wt%, 2.8wt%, 2.9wt%, 3.0wt%, 3.1wt%, 3.2wt%, 3.3wt%, 3.4wt%, 3.5wt%, 3.6wt%, 3.7wt%, 3.8wt%, 3.9wt%, 4.0wt%, 4.1wt%, 4. 2wt%, 4.3wt%, 4.4wt%, 4.5wt%, 4.6wt%, 4.7wt%, 4.8wt%, 4.9wt%, 5.0wt%, 5.5wt%, 6.0wt%, 6.5wt%, 7.5wt%, 8.0wt%, 8.5wt%, 9.0wt%, 9.5wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt %, 21wt%, 22wt%, 23wt%, 24wt%, 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt%, 31wt%, 3 2wt%, 33wt%, 34wt%, 35wt%, 36wt%, 37wt%, 38wt%, 39wt%, 40wt%, 41wt%, 42wt%, 43wt %, 44wt%, 45wt%, 46wt%, 47wt%, 48wt%, 49wt%, 50wt%, 51wt%, 52wt%, 53wt%, 54wt%, 5 %, 56wt%, 57wt%, 58wt%, 59wt%, 60wt%, 61wt%, 62wt%, 63wt%, 64wt%, 65wt%, 66wt%, 67wt%, 68wt%, 69wt%, 70wt%, 71wt%, 72wt%, 73wt%, 74wt%, 75wt%, 76wt%, 77wt%, 78wt%, 79wt%, 80wt%, 81wt%, 82wt%, 83wt%, 84wt%, 85wt%, 86wt%, 87wt%, 88wt%, 89wt%, 90wt%, 91wt%, 92wt%, 93wt%, 94wt%, 95wt%, 96wt%, 97wt%, 98wt%, 99wt% and 99.9wt%. .

[0030] According to ISO 1133 standard, the MFI of PBT at 250°C and 2.16 kg load is 0.1g / 10min to 40 / 10min, or according to ISO 1133 standard, at least the following, equal to the following and / or between any two of the following values: 0.1g / 10min, 0.2g / 10min, 0.3g / 10min, 0.4g / 10min, 0.5g / 10min, 0.6g / 10min, 0.7g / 10min, 0.8g / 10min, 0.9g / 10min, 1g / 10min, 2g / 10min, 3g / 10min, 4g / 10min, 5g / 10min, 6g / 10min, 7g / 10min, 8g / 10min, 9g / 10min, 10g / 10min, 11g / 10min, 12g / 10min, 13g / 10min, 14g / 10min, 15g / 10min, 16g / 10min, 17g / 10min, 18g / 10min, 19g / 10min, 20g / 10min, 21g / 10min, 22g / 10min 9g / 10min and 20g / 10min, 21g / 10min, 22g / 10min, 23g / 10min, 24g / 10min, 25g / 10min, 26g / 10min, 27g / 10min, 28g / 10min, 29g / 10min, 30g / 10min, 31g / 10min, 32g / 10min, 33g / 10min, 34g / 10min, 35g / 10min, 36g / 10min, 37g / 10min, 38g / 10min, 39g / 10min and 40g / 10min.

[0031] The polydispersity index (PDI=Mw / Mn) of the PBT component as measured by high temperature gel permeation chromatography may be 2 to 10, or at least the following, equal to the following, and / or between any two of the following values: 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, 6.2, 6.3, 6.4, 6.5, 6.6, 6.7, 6.8, 6.9, 7.0, 7.1, 7.2, 7.3, 7.4, 7.5, 7.6, 7.8, 7.9, 8.0, 8.1 1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, 6.2, 6.3, 6.4, 6.5, 6.6, 6.7, 6.8, 6.9, 7.0, 7.1, 7.2, 7.3, 7.4, 7.5, 7.6, 7.7, 7.8, 7.9, 8.0, 8.1, 8.2, 8.3, 8.4, 8.5, 8.6, 8.7, 8.8, 8.9, 9.0, 9.1, 9.2, 9.3, 9.4, 9.5, 9.6, 9.7, 9.8, 9.9 and 10.0.

[0032] The tensile modulus of PBT can be 1700 MPa to 3000 MPa, or at least 1700 MPa, 1750 MPa, 1800 MPa, 1850 MPa, 1900 MPa, 1950 MPa, 2000 MPa, 2050 MPa, 2100 MPa, 2150 MPa, 2200 MPa, 2250 MPa, 2300 MPa, 2350 MPa, 2400 MPa, 2450 MPa, 2500 MPa, 2550 MPa, 2600 MPa, 2650 MPa, 2700 MPa, 2750 MPa, 2800 MPa, 2850 MPa, 2900 MPa, 2950 MPa, and 3000 MPa, as measured by ASTM D638. The yield tensile strength of PBT measured by ISO527 can be 20 MPa to 60 MPa, or at least, equal to, and / or between any two of the following: 20 MPa, 25 MPa, 30 MPa, 35 MPa, 40 MPa, 45 MPa, 50 MPa, 55 MPa, and 60 MPa.

[0033] The Izod notched impact strength of the PBT component at -30°C can be 2 kJ / m 2 Up to 8kJ / m 2 , at least the following, equal to the following and / or between any two of the following: 3 kJ / m 2 , 4kJ / m 2 , 5kJ / m 2 and 6 kJ / m2 , 7kJ / m 2 and 8kJ / m 2 The Izod notched impact strength of the PBT component at 23°C can be 4 kJ / m 2 to 15 kJ / m2, or at least the following, equal to the following and / or between any two of the following: 4 kJ / m 2 , 5kJ / m 2 , 6kJ / m 2 , 7kJ / m 2 , 8kJ / m 2 , 9kJ / m 2 , 10kJ / m2, 11kJ / m 2 、12kJ / m 2 、13kJ / m 2 、14kJ / m 2 and 15 kJ / m 2 22kJ / m 2 , as measured by ISO180.

[0034] As described above, PBT compositions are used as polymer blends in combination with one or more different primary additives for high frequency radio wave applications. These primary additives can provide the PBT composition with lower Dk, lower Df, higher metal adhesion strength, and lower CTE than PBT without such additives. PBT compositions can also exhibit higher mechanical strength and good thermal properties.

[0035] The main additives include hollow glass bubbles. These glass bubbles help reduce the bulk density of PBT and lower the Dk and Df values. This is at least in part due to the lower Dk and Df values ​​of the glass bubbles themselves due to the presence of air, gas or vacuum space within the glass bubbles.

[0036] Glass bubbles are generally hollow thin-walled single-cell spheres made of soda-lime borosilicate glass. The average diameter or particle size of the glass bubbles is 5 μm to 80 μm, especially the average diameter or particle size is 15 μm to 65 μm. In certain embodiments, the average diameter or particle size of the glass bubbles may be at least the following, equal to the following, and / or between any two of the following values: 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm and 20 μm, 21 μm, 22 μm, 23 μm, 24 μm, 25 μm, 26 μm, 27 μm, 28 μm, 29 μm, 30 μm, 31 μm, 32 μm, 33 μm, 34 μm, 35 μm, 36 μm, 37 μm, 38 μm m, 39μm, 40μm, 41μm, 42μm, 43μm, 44μm, 45μm, 46μm, 47μm, 48μm, 49μm, 50μm, 51μm, 52μm, 53μm, 54μm, 55μm, 56μm, 57μm, 58μm, 59μm , 60μm, 61μm, 62μm, 63μm, 64μm, 65μm, 66μm, 67μm, 68μm, 69μm, 70μm, 71μm, 72μm, 73μm, 74μm, 75μm, 76μm, 77μm, 78μm, 79μm and 80μm.

[0037] The wall thickness of the hollow glass bubble can be 0.4 μm to 1.5 μm, more specifically 0.5 μm to 0.9 μm, and even more specifically 0.6 μm to 0.8 μm. In a specific embodiment, the glass bubble can have a wall thickness of at least, equal to, and / or between any two of the following: 0.40 μm, 0.41 μm, 0.42 μm, 0.43 μm, 0.44 μm, 0.45 μm, 0.46 μm, 0.47 μm, 0.48 μm, 0.49 μm, 0.50 μm, 0.51 μm, 0.52 μm, 0.53 μm, 0.54 μm, 0.55 μm, 0.56 μm, 0.57 μm, 0.58 μm, 0.59 μm, 0.60 μm, 0.61μm, 0.62μm, 0.63μm, 0.64μm, 0.65μm, 0.66μm, 0.67μm, 0.68μm, 0.69μm, 0.70μm, 0.71μm, 0.72μm, 0.73μm, 0.74μm, 0.75μm, 0.76μm, 0.77μm, 0.78μm, 0.79μm, 0.80μm, 0.81μm, 0.82μm, 0.83μm, 0.84μm, 0.85μm, 0.86μm, 0.8 7μm, 0.88μm, 0.89μm, 0.90μm, 0.91μm, 0.92μm, 0.93μm, 0.94μm, 0.95μm, 0.96μm, 0.97μm, 0.98μm, 0.99μm, 1.00μm m, 1.11μm, 1.12μm, 1.13μm, 1.14μm, 1.15μm, 1.16μm, 1.17μm, 1.18μm, 1.19μm, 1.20μm, 1.21μm, 1.22μm, 1.23μm, 1 .24μm, 1.25μm, 1.26μm, 1.27μm, 1.28μm, 1.29μm, 1.30μm, 1.31μm, 1.32μm, 1.33μm, 1.34μm, 1.35μm, 1.36μm, 1.37 μm, 1.38μm, 1.39μm, 1.40μm, 1.41μm, 1.42μm, 1.43μm, 1.44μm, 1.45μm, 1.46μm, 1.47μm, 1.48μm, 1.49μm and 1.50μm.

[0038] This can provide 50% to about 90% of the gas volume or internal space in the hollow glass sphere. It has been found that those glass bubbles with 60% to 80% gas volume or internal space are particularly useful. In a particular embodiment, the gas volume or internal space in the hollow glass bubble can be at least the following, equal to the following and / or between any two values ​​of the following: 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89% and 90%. The inner space of the glass bubble is usually filled with air, but can also be filled with other gases, such as nitrogen. The inner space can also be free of any medium (vacuum) or filled with a low dielectric liquid that is beneficial to reducing the Dk and Df values.

[0039] The glass bubbles may have a true density of 0.3 g / cc to 0.8 g / cc as measured by helium pycnometry. In certain embodiments, the glass bubbles may have a true density of at least, equal to, and / or between any two of the following as measured by helium pycnometry: 0.30 g / cc, 0.31 g / cc, 0.32 g / cc, 0.33 g / cc, 0.34 g / cc, 0.35 g / cc, 0.36 g / cc, 0.37 g / cc, 0.38 g / cc, 0.39 g / cc, 0.40 g / cc, 0.41 g / cc, 0.42 g / cc, 0.43 g / cc, 0.44 g / cc, 0.45 g / cc, 0.46 g / cc, 0.47 g / cc, 0.48 g / cc, 0.49 g / cc, 0.50 g / cc, 0.51 g / cc, 0.52 g / cc, 0.53 g / cc, 0.54 g / cc, 0.55 g / cc, 0.56 g / cc, 0.57 g / cc, 0.58 g / cc, 0.59 g / cc, 0.60 g / cc, 0.61 g / cc, 0.62 g / cc, 0.63 g / cc, 0.64 g / cc, 0.65 g / cc, 0.66 g / cc, 0.67 g / cc, 0.68 g / cc, 0.69 g / cc, 0.70 g / cc, 0.71 g / cc, 0.72 g / cc, 0.73 g / cc, 0.74 g / cc g / cc, 0.53g / cc, 0.54g / cc, 0.55g / cc, 0.56g / cc, 0.57g / cc, 0.58g / cc, 0.59g / cc, 0.60g / cc, 0.61g / cc, 0.62g / cc, 0.63g / cc, 0.64g / cc, 0.65g / cc, 0.66g / cc, 0.67g / cc, 0.68g / cc, 0.69g / cc, 0.70g / cc, 0.71g / cc, 0.72g / cc, 0.73g / cc, 0.74g / cc, 0.75g / cc, 0.76g / cc, 0.77g / cc, 0.78g / cc, 0.79g / cc, 0.80g / cc.

[0040] In addition, the hollow glass bubbles may have a crushing strength of 30 MPa to 300 MPa. In a specific embodiment, the glass bubbles may have a crushing strength of at least, equal to, and / or between any two of the following values: 30 MPa, 31 MPa, 32 MPa, 33 MPa, 34 MPa, 35 MPa, 36 MPa, 37 MPa, 38 MPa, 39 MPa, 40 MPa, 41 MPa, 42 MPa, 43 MPa, 44 MPa, 45 MPa, 46 MPa, 47 MPa, 48 MPa, 49 MPa, 50 MPa, 51 MPa, 52 MPa, 53 MPa, 54 MPa, 55 MPa, 56 MPa, 57 MPa, 58 MPa, 59 MPa, 60 MPa, 61 MPa, 62 MPa, 63 MPa, 64 MPa, 65 MPa, 66 MPa, 67 MPa, 68 MPa, 69 MPa, 70 MPa, 71 MPa, 72 MPa, 73 MPa, 74 MPa, 75 MPa, 76 MPa, 77 MPa, 78 MPa, 79 MPa, 80 MPa, 81 MPa, 82 MPa, 83 MPa, 84 MPa 2MPa, 53MPa, 54MPa, 55MPa, 56MPa, 57MPa, 58MPa, 59MPa, 65MPa, 66MPa, 67MPa, 68MPa, 69MPa, 70MPa, 71MPa, 7 2MPa, 73MPa, 74MPa, 75MPa, 76MPa, 77MPa, 78MPa, 79MPa, 80MPa, 81MPa, 82MPa, 83MPa, 84MPa, 85MPa, 86MPa, 87 MPa, 88MPa, 89MPa, 90MPa, 91MPa, 92MPa, 93MPa, 94MPa, 95MPa, 96MPa, 97MPa, 98MPa, 99MPa, 100MPa, 105MPa, 110MPa, 115MPa, 120MPa, 125MPa, 130MPa, 135MPa, 140MPa, 145MPa, 150MPa, 155MPa, 160MPa, 165MPa, 170MPa, 175MPa, 180MPa, 185MPa, 190MPa, 195MPa, 200MPa, 205MPa, 210MPa, 215MPa, 220MPa, 225MPa, 230MPa, 235MPa, 240MPa, 245MPa, 250MPa, 255MPa, 260MPa, 265MPa, 270MPa, 275MPa, 280MPa, 285MPa, 290MPa, 295MPa and 300MPa.

[0041] Examples of suitable commercially available hollow glass bubbles include iM16K and iM30K glass bubbles, available from 3M Company, Maplewood, Minnesota. The glass bubbles used in this study (IM30K high strength glass bubbles) were purchased from 3M TM The squeeze strength and gas volume of the hollow glass bubble were measured by 3M's in-house QCM.

[0042] The amount of the hollow glass bubbles in the PBT composition is 1 wt% to 35 wt%, based on the total weight of the PBT composition. In a specific embodiment, the amount of the hollow glass bubbles in the PBT composition is at least, equal to, and / or between any two of the following values: 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, 15 wt%, 16 wt%, 17 wt%, 18 wt%, 19 wt%, 20 wt%, 21 wt%, 22 wt%, 23 wt%, 24 wt%, 25 wt%, 26 wt%, 27 wt%, 29 wt%, 30 wt%, 31 wt%, 32 wt%, 33 wt%, 34 wt%, and 35 wt%, based on the total weight of the PBT composition.

[0043] During the melt mixing process of the polymer composition, a certain amount of glass bubble breakage may occur. This will typically result in 5% or less glass bubble breakage. Although glass bubble breakage should be minimized, these broken glass bubbles will essentially become glass powder, which helps to strengthen the PBT composition.

[0044] Since glass bubbles and / or broken glass bubbles by themselves do not provide sufficient reinforcement for PBT compositions, other materials may also be used in PBT compositions. These materials include short glass fiber (SGF) materials and alumina fiber materials.

[0045] Glass fibers can be used to enhance the mechanical and thermal properties of PBT compositions. This includes higher stiffness, higher tensile or flexural modulus, lower CTE, higher heat distortion temperature (HDT), and better dimensional stability. Short glass fibers may also include those with low Dk and / or Df values, so that the reinforcement provided by the glass bubbles to the low Dk and Df polymer composition is enhanced, or not significantly reduced or altered.

[0046] The length of the short glass fiber is 0.5mm to 10mm, and the width or diameter is 5μm to 15μm. In a specific application, the length of the short glass fiber is at least the following, equal to the following and / or between any two of the following values: 0.6mm, 0.7mm, 0.8mm, 0.9mm, 1.0mm, 1.1mm, 1.2mm, 1.3mm, 1.4mm, 1.5mm, 1.6mm, 1.7mm, 1.8mm, 1.9mm, 2.0mm, 2.1mm, 2.2mm, 2.3mm, 2.4mm m, 2.5mm, 2.6mm, 2.7mm, 2.8mm, 2.9mm, 3.0mm, 3.1mm, 3.2mm, 3.3mm, 3.4mm, 3.5mm, 3.6mm, 3. 7mm, 3.8mm, 3.9mm, 4.0mm, 4.1mm, 4.2mm, 4.3mm, 4.4mm, 4.5mm, 4.6mm, 4.7mm, 4.8mm, 4.9mm, 5 .0mm, 5.1mm, 5.2mm, 5.3mm, 5.4mm, 5.5mm, 5.6mm, 5.7mm, 5.8mm, 5.9mm, 6.0mm, 6.1mm, 6.2mm , 6.3mm, 6.4mm, 6.5mm, 6.6mm, 6.7mm, 6.8mm, 6.9mm and 7.0mm, 7.1mm, 7.2mm, 7.3mm, 7.4mm, 7.5m The width or diameter of the short glass fibers may be at least 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, and 15 μm.

[0047] The amount of short glass fiber in the PBT composition can be 40wt% or less of the total weight of the PBT composition. In many cases, 1wt% to 30wt% of the total weight of the PBT composition is suitable. In a specific embodiment, the amount of glass fiber can be at least the following, equal to the following and / or between any two of the following values, calculated based on the total weight of the PBT composition: 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt%, 31wt%, 32wt%, 33wt%, 34wt%, 35wt%, 36wt%, 37wt%, 38wt%, 39wt%, 40wt%, 41wt%, 42wt%, 43wt%, 44wt%, 45wt%, 46wt%, 47wt%, 48wt%, 49wt%, 50wt%, 51wt%, 52wt%, 53wt%, 54wt%, 55wt%, 56wt%, 57wt%, 58wt%, 59wt%, 60wt%, 61wt%, 62wt%, 63wt%, 64wt%, 65wt%, 66wt%, 67wt%, 68wt%, 69wt%, 70wt%, 71 wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt %, 26wt%, 27wt%, 29wt%, 30wt%, 31wt%, 32wt%, 33wt%, 34wt%, 35wt%, 36wt%, 37wt%, 38wt%, 39wt% and 40wt%.

[0048] The CTE value of the PBT composition containing short glass fibers is 35 x 10 -6 In certain embodiments, the CTE value of the PBT composition containing short glass fibers can be 35, 30, 25, 20, 15, 10, 9, 8, 7, 6, 5, 4, 3, 2, 1, or 0.5X 10 -6 / ℃ or lower.

[0049] In some applications, the short glass fibers may be glass fibers with higher or lower Dk and Df values, because both low Dk and high Df glass fibers can provide similar reinforcement effects for PBT compositions. If short glass fibers with higher Dk and Df values ​​are used, they may be those having a Dk value of 5 or higher measured at 6 MHz or higher according to ASTM D150, and a dissipation factor Dk greater than 0.005 measured at 6 MHz or higher according to ASTM D150. Such glass fibers may include E-CR (E-glass corrosion resistant) glass fibers. For example, DS2200 13P glass fibers produced by the Braj Binani Group in Mumbai, India, are such commercially available short glass fibers. These glass fibers are different from those having lower Dk and Df values. These glass fibers are different from glass fibers having lower Dk and Df values.

[0050] Glass fibers with low dielectric values ​​or Dk and Df values ​​may also be used alone or in combination with short glass fibers with higher Dk and Df values. Low Dk glass fibers may be glass fibers having a Dk value of 4 to 5 measured at 6 MHz or higher according to ASTM D150. In certain embodiments, the Dk value of the low Dk glass fiber may be at least, equal to, and / or between any two of the following: 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, and 5.0. Low Df glass fibers can be glass fibers having a Df value of 0.005, 0.004, 0.003, 0.002, 0.001, 0.0009, 0.0008, 0.0007, 0.0006, 0.0005, 0.0004, 0.0003, 0.0002, 0.0001 or less. Low Dk and low Df glass fibers can have one or both low Dk and low Df. Typically, low Dk and Df glass fibers have both low Dk and low Df. Such glass fibers may include HL glass fibers. An example of such commercially available short glass fibers having a low Dk value and a low Df value is the CS (HL) 303N-3 glass fiber produced by Chongqing Polycomp International, China.

[0051] Low Dk and low Df glass fibers may account for all or part of all short glass fibers. The content of low Dk and low Df glass fibers in the PBT composition may be 40% or less of the total weight of the PBT composition. In a specific embodiment, if used, the amount of low Dk and low Df glass fibers, calculated based on the total weight of the PBT composition, may be at least the following, equal to the following and / or between any two of the following values: 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt%, 31wt%, 32wt%, 33wt%, 34wt%, 35wt%, 36wt%, 37wt%, 38wt%, 39wt%, 40wt%, 41wt%, 42wt%, 43wt%, 44wt%, 45wt%, 46wt%, 47wt%, 48wt%, 49wt%, 50wt%, 51wt%, 52wt%, 53wt%, 54wt%, 55wt%, 56wt%, 57wt%, 58wt%, 59wt%, 60wt%, 61wt%, 62wt%, 63wt%, 64wt%, 65wt%, 66wt%, 67wt%, 68wt%, 69wt%, 70wt%, 71 wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 2 5wt%, 26wt%, 27wt%, 29wt%, 30wt%, 31wt%, 32wt%, 33wt%, 34wt%, 35wt%, 36wt%, 37wt%, 38wt%, 39wt% and 40wt%.

[0052] Alumina fibers can be used in PBT compositions. Alumina fibers can enhance mechanical properties such as tensile modulus and stiffness while maintaining radio frequency (RF) transparency. Alumina fibers can be any form of aluminum oxide phase and can be obtained by any suitable process. Alumina fibers can be cylindrical and / or flat. Alumina fibers can have a length between 1 mm and 10 mm and a diameter or width between 1 μm and 15 μm. In certain applications, the length of the alumina fibers may be at least the following, equal to the following and / or between any two of the following values: 1.0 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.5 mm, 1.6 mm, 1.7 mm, 1.8 mm, 1.9 mm, 2.0 mm, 2.1 mm, 2.2 mm, 2.3 mm, 2.4 mm, 2.5 mm, 2.6 mm, 2.7 mm, 2.8 mm, 2.9 mm, 3.0 mm, 3.1 mm, 3.2 mm, 3.3 mm, 3.4 mm, 3.5 mm, 3.6 mm, 3.7 mm, 3.8 mm, 3.9 mm, 4.0 mm, 4.1 mm, 4.2 mm, 4.3 mm, 4.4 mm, 4.5 mm, 4.6 mm, 4.7 mm, 4.8 mm, 4.9 mm, 5.0 mm, 5.1 mm, 5.2 mm, 5.3 mm, 5.4 mm, 5.5 mm, 5.6 mm, 5.7 mm, 5.8 mm, 5.9 mm, 6.0 mm, 6.1 mm, 6.2 mm, 6.3 mm, 6.4 mm, 6.5 mm, 6.6 mm, 6.7 mm, 6.8 mm, 6.9 mm, 7. 5.2mm, 5.3mm, 5.4mm, 5.5mm, 5.6mm, 5.7mm, 5.8mm, 5.9mm, 6.0mm, 6.1mm, 6.2mm, 6.3mm, 6 .4mm, 6.5mm, 6.6mm, 6.7mm, 6.8mm, 6.9mm and 7.0mm, 7.1mm, 7.2mm, 7.3mm, 7.4mm, 7.5mm, 7.6 The width or diameter of the alumina fibers may be at least, equal to, and / or between any two of the following: 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, and 15 μm. For example, Nextel 610 fiber manufactured by 3M Company in Maplewood, Minnesota is such a commercially available alumina fiber.

[0053] The content of alumina fiber in the PBT composition can be 40wt% or less, based on the total weight of the PBT composition. If used, in certain embodiments, the amount of alumina fiber can be at least the following, equal to the following, and / or between any two of the following values: 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt%, 31wt%, 32wt%, 33wt%, 34wt%, 35wt%, 36wt%, 37wt%, 38wt%, 39wt%, 40wt%, 41wt%, 42wt%, 43wt%, 44wt%, 45wt%, 46wt%, 47wt%, 48wt%, 49wt%, 50wt%, 51wt%, 52wt%, 53wt%, 54wt%, 55wt%, 56wt%, 57wt%, 58wt%, 59wt%, 60wt%, 61wt%, 62wt%, 63wt%, 64wt%, 65wt%, 66wt%, 67wt%, 68wt%, 69wt%, 70wt%, 71wt%, 72wt%, 73wt%, 74wt%, 75wt%, 76wt%, 77wt%, 78wt%, 79wt%, %, 35wt%, 36wt%, 37wt%, 38wt%, 39wt% and 40wt% (calculated based on the total weight of the PBT composition).

[0054] In some applications, polyethylene terephthalate (PET) is used in combination with PBT. According to ASTM D1895, the inherent viscosity of the PET used is between 0.5 dl / g and 0.8 dl / g, and the bulk density is 800 kg / m 3 Up to 850kg / m 3 If used, any PET component is present in an amount of 30 wt% or less based on the total weight of the composition. In certain embodiments, the amount of PET, if used, can be at least 0.1 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.8 wt%, 0.9 wt%, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, 15 wt%, 16 wt%, 17 wt%, 18 wt%, 19 wt%, 20 wt%, 21 wt%, 22 wt%, 23 wt%, 24 wt%, 25 wt%, 26 wt%, 27 wt%, 29 wt%, and 30 wt%, based on the total weight of the PBT composition. An example of such commercially available PET is BC210, BC211, BC212, PCG 60 and PCG 80, available from Saudi Basic Industries Corporation in Riyadh, Saudi Arabia. In certain applications, PET is not used in the PBT composition.

[0055] Polycarbonates can also be used in PBT compositions. The weight average molecular weight of polycarbonate is between 30,000 and 60,000 as inferred by gel permeation chromatography, which meets polystyrene standards. Polycarbonate has full end caps as inferred by nuclear magnetic resonance analysis. Polycarbonate can improve metal adhesion and reduce warpage. Such polycarbonates include, but are not limited to, bisphenol A polycarbonate and copolycarbonates of different comonomer ratios (e.g., 20% to 50%). Particularly useful is bisphenol-A polycarbonate.

[0056] The polycarbonate may be used in an amount of 30 wt % or less based on the total weight of the PBT composition, with or without a transesterification catalyst. If used, in certain embodiments, the polycarbonate can be used in an amount of at least, equal to, and / or between any two of the following values, based on the total weight of the PBT compound: 0.1 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.8 wt%, 0.9 wt%, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, 15 wt%, 16 wt%, 17 wt%, 18 wt%, 19 wt%, 20 wt%, 21 wt%, 22 wt%, 23 wt%, 24 wt%, 25 wt%, 26 wt%, 27 wt%, 28 wt%, 29 wt%, and 30 wt%.

[0057] The PBT composition or polymer blend formed during the melt mixing process may further include at least one additional auxiliary additive, distinct from the primary additives discussed above. These optional or auxiliary additives may be additives that do not necessarily affect or increase the dielectric properties (i.e., Dk and Df values), mechanical properties, or thermal properties of the final product, although they may affect them. These additives may be added to facilitate processing during melt mixing and extrusion, but may also bring various desired properties to the final PBT composition. Non-limiting examples of additional optional or auxiliary additives include stabilizers, coupling agents, compatibilizers, thermal conductors, flame retardant additives, thermal conductive additives, adhesives, anti-blocking agents, antistatic agents, antioxidants, neutralizers, acid scavengers, foaming agents, nucleating agents, crystallizing agents, nucleating agents, crystallization aids, dyes, flame retardants, fillers, hard fillers, soft fillers, impact modifiers, mold release agents, oils, another polymer, pigments, processing agents, reinforcing agents, light stabilizers, UV inhibitors, slip agents, flow modifiers, and combinations thereof.

[0058] Since PBT has polar functional groups throughout the polymer chain, this may promote the dispersion of glass bubbles, glass fibers, polycarbonate, etc. in the entire polymer mixture. Therefore, the use of coupling agents in the polymer mixture to achieve a good interface with glass bubbles and fibers may be reduced or eliminated. However, in some embodiments, a coupling agent may be used in the PBT component or the glass fiber. The glass fiber can be treated with a silane coupling agent to further improve the uniform dispersion of these materials in the PBT matrix. The coupling agent can be maleic anhydride grafted PBT (MA-g-PP). The coupling is performed in situ in the extruder. After using this coupling agent, the interaction between the maleic anhydride groups and the amino groups on the aminosilane-treated glass fibers can promote the dispersion of the glass fibers. An example of a coupling agent suitable for PBT is maleic anhydride grafted polypropylene (MA-g-PP), such as EXELOR P1020 from ExxonMobil. The coupling agent may be present in the polymer mixture at 2 wt% or less of the total weight of the polymer mixture. In certain embodiments, if a coupling agent is used, the amount thereof may be at least, equal to, and / or between any two of the following: 0.01 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.8 wt%, 0.9 wt%, 1.0 wt%, 1.1 wt%, 1.2 wt%, 1.3 wt%, 1.4 wt%, 1.5 wt%, 1.6 wt%, 1.7 wt%, 1.8 wt%, 1.9 wt%, and 2.0 wt% (based on the total weight of the polymer mixture). When polycarbonate is incorporated into PBT, an ester exchange catalyst (such as p-toluenesulfonic acid) may be added to achieve reactive coupling between PBT and polycarbonate. The amount of the ester exchange catalyst used ranges from 0.001 wt% to 0.01 wt%, based on the total weight of the polymer mixture.

[0059] In some cases, the amount of thermally conductive additive in the polymer blend is at least, equal to, and / or between any two of the following values, based on the total weight of the polymer mixture: 0.01 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.8 wt%, 0.9 wt% and 1.0 wt%. Non-limiting examples of thermally conductive additives include: aluminum oxide, titanium dioxide, graphite compounds, graphene, boron nitride, aluminum nitride, zinc oxide.

[0060] In some embodiments, the filler is present in the polymer mixture in an amount of at least, equal to, and / or between any two of the following values: 0.01 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.8 wt%, 0.9 wt%, 1.0 wt%, 2.0 wt%, 3.0 wt%, 4.0 wt%, 5.0 wt%, 6.0 wt%, 7.0 wt%, 8.0 wt%, 9.0 wt%, 10.0 wt%, 20.0 wt%, 30.0 wt% (calculated by the total weight of the polymer mixture). The filler can be a hard filler. Non-limiting examples of hard fillers include inorganic particulate fillers such as talc, silica, calcium carbonate, and inorganic layered fillers such as clay and mica. The filler can be a soft filler. Non-limiting examples of soft fillers include incompatible particulate elastomers / polymer resins. The filler can also be a hollow filler. Non-limiting examples of hollow fillers include plastic microspheres, ceramic microspheres (such as hollow spheres composed of aluminum silicate microspheres), metal microspheres composed of aluminum and copper / silver microspheres, and phenolic microspheres.

[0061] In certain aspects, the light stabilizer is present in the polymer mixture in an amount of at least, equal to, and / or between any two of the following values, based on the total weight of the polymer mixture: 0.01 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.8 wt%, 0.9 wt%, and 1.0 wt%. The light stabilizer can be a hindered amine light stabilizer. The term "hindered amine light stabilizer" refers to a class of amine compounds having certain light stabilizing properties. Non-limiting examples of hindered amine light stabilizers (HALS) include 1-cyclohexyloxy-2,2,6,6-tetramethyl-4-octadecylaminopiperidine; bis(2,2,6,6-tetramethylpiperidin-4-yl) sebacate; bis(1-acetoxy-2,2,6-tetramethylpiperidin-4-yl) sebacate; bis(1,2,2,6-pentamethylpiperidin-4-yl) sebacate; bis(1-cyclohexyloxy-2,2,6-tetramethylpiperidin-4-yl) sebacate; bis(1-octyloxy-2,2,6,6-tetramethylpiperidin-4-yl) sebacate; bis(1-acetyloxy-2,2,6-tetramethylpiperidin-4-yl) sebacate; bis(1,2,2,6-pentamethyl-4-piperidinyl)butylamino]-6-(2-hydroxyethylamino)-s-triazine; bis(1-cyclohexyloxy-2,2,6-tetramethylpiperidin-4-yl)adipate; 2-bis[(1-cyclohexyloxy-2,2,6-piperidin-4-yl)butylamino]-6-chloro-s-triazine; 1-(2-hydroxy-2-methylpropoxy) -4-hydroxy-2,2,6-tetramethylpiperidine; 1-(2-hydroxy-2-methylpropoxy)-4-oxo-2,2,6-tetramethylpiperidine; 1-(2-hydroxy-2-methylpropoxy)-4-octadecyloxy-2,2,6-tetramethylpiperidine; bis(1-(2-hydroxy-2-methylpropoxy)-2,2,6,6-tetramethylpiperidin-4-yl) sebacate; bis(1-(2-hydroxy-2-methylpropoxy)-2,2,6,6-tetramethylpiperidin-4-yl) adipate; 2,4-bis{N-[1-(2-hydroxy-2-methylpropoxy)-2,2, 6-Tetramethylpiperidin-4-yl]-N-butylamino}-6-(2-hydroxyethylamino)-s-triazine; 4-benzoyl-2,2,6-tetramethylpiperidine; di-(1,2,2,6-pentamethylpiperidin-4-yl)-p-methoxybenzylidenemalonate; 2,2,6,6-tetramethylpiperidin-4-yl octadecanoate; bis(1-octyloxy-2,2,6-tetramethylpiperidinyl)succinate; 1,2,2,6-pentamethyl-4-aminopiperidine; 2-Undecyl-7,7,9-tetramethyl-1-oxa-3,8-diaza-4-oxo-spiro[4,5]decane;Tris(2,2,6,6-tetramethyl-4-piperidinyl) nitrilotriacetate; Tris(2-hydroxy-3-(amino-(2,2,6,6-tetramethylpiperidin-4-yl)propyl) nitrilotriacetate; Tetrakis(2,2,6,6-tetramethyl-4-piperidinyl)-1,2,3,4-butane-tetracarboxylate; Tetrakis(1,2,2,6-pentamethyl-4-piperidinyl)-1,2,3,4-butane-tetracarboxylate; 1,1′-(1,2-ethanediyl)-bis(3,3,5,5-tetramethylpiperazinone); 3-octyl-7,7,9-tetramethyl-1,3,8-triazaspiro[4.5]decane-2,4-dione; 8-acetyl-3-dodecyl-7,7,9 -tetramethyl-1,3,8-triazaspiro[4.5]decane-2,4-dione; 3-dodecyl-1-(2),2,6-tetramethyl-4-piperidinyl)pyrrolidine-2,5-dione; 3-dodecyl-1-(1),2,2,6,6-pentamethyl-4-piperidinyl)pyrrolidine-2,5-dione; N,N′-bis-formyl-N,N′-bis(2,2,6,6-tetramethyl-4-piperidinyl)hexamethylenediamine; 2-bis[(1-cyclohexyloxy-2,2,6-piperidin-4-yl)butylamino]-6-chloro-s-triazine, reaction products with N,N′-bis(3-aminopropyl)ethylenediamine; 1-(2-hydroxyethyl)-2,2,6,6-tetramethyl- Condensate of 4-hydroxypiperidine and succinic acid; Condensate of N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-hexanediamine and 4-tert-octylamino-2,6-dichloro-3,3-triazine; Condensate of N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-hexanediamine and 4-cyclohexylamino-2,6-dichloro-3,3-triazine; Condensate of N,N'-bis-(2,2,6,6-tetramethyl-4-piperidinyl)hexamethylenediamine and 4-morpholino-2,6-dichloro-3,3-triazine; Condensate of N,N'-bis-(1,2,2,6-pentamethyl-4-piperidinyl)hexamethylenediamine and 4-morpholino-2,6-dichloro-3,3-triazine 2-Chloro-4,6-bis(4-n-butylamino-2,2,6,6-tetramethylpiperidinyl)-3,3-triazine and 1,2-bis(3-aminopropylamino)ethane condensate; 2-Chloro-4,6-di-(4-n-butylamino-1,2,2,6-pentamethylpiperidinyl)-1,3-triazine and 1,2-bis-(3-aminopropylamino)ethane condensate; 7,7,9,9-tetramethyl-2-cycloundecyl-1-oxa-3,8-diaza-4-oxaspiro[4,5]decane reaction products with epichlorohydrin; Poly[methyl,(3-oxy-(2,2,6,6-tetramethylpiperidin-4-yl)propyl)]siloxane, CAS#182635-99-0;Reaction products of maleic anhydride-C18-C22-alpha-olefin copolymers with 2,2,6,6-tetramethyl-4-aminopiperidine; low molecular weight derivatives of 4,4′-hexamethylenebis(amino-2,2,6-tetramethylpiperidine) and 2,4-dichloro-6-[(2,6,6-tetramethylpiperidin-4-yl)butylamino]-s-triazine terminated with 2-chloro-4,6-bis(dibutylamino)-s-triazine; Polycondensate; oligomeric condensate of 4,4′-hexamethylenebis(amino-1,2,2,6,6-pentamethylpiperidine) and 2,4-dichloro-6-[(1,2,6,6-pentamethylpiperidin-4-yl)butylamino]-s-triazine terminated with 2-chloro-4,6-bis(dibutylamino)-s-triazine; oligomeric condensate of 4,4′-hexamethylenebis(amino-1-propoxy-2,2,6,6-tetramethyl Oligomeric condensates of 2,4-dichloro-6-[(1-propoxy-2,2,6,6-tetramethylpiperidin-4-yl)butylamino]-s-triazine terminated with 2-chloro-4,6-bis(dibutylamino)-s-triazine; 4,4'-hexamethylenebis(amino-1-acyloxy-2,2,6,6-tetramethylpiperidine) and 2,4-dichloro-6-[(1-propoxy-2,2,6,6-tetramethylpiperidin-4-yl)butylamino]-s-triazine terminated with 2-chloro-4,6-bis(dibutylamino)-s-triazine Oligomeric condensates of blocked 2,4-dichloro-6-[(1-acyloxy-2,2,6,6-tetramethylpiperidin-4-yl)butylamino]-s-triazine; and products obtained by reacting (a) with (b), wherein (a) is the product obtained by reacting 1,2-bis(3-aminopropylamino)ethane with cyanuric acid chloride, and (b) is (2,6-tetramethylpiperidin-4-yl)butylamine. Also included are sterically hindered NH, N-methyl, N-methoxy, N-hydroxy, N-propoxy, N-octyloxy, N-cyclohexyloxy, N-acyloxy and N-(2-hydroxy-2-methylpropoxy) analogs of any of the above compounds. Non-limiting examples of commercial light stabilizers can be found under the trade names; 4050H, 4077H, 4092H, 5062H, 5050H, 4092H, 4077H, 3026, 3027, 3028, 3029, 3033P and 3034 or 622, purchased from BASF.

[0062] Antistatic agents can be used to inhibit the accumulation of dust on plastic products. Antistatic agents can increase the conductivity of plastic compositions, thereby dissipating any surface charge generated during production and use. In this way, the attraction of the surface of the plastic product to dust particles will be reduced, thereby reducing the accumulation of dust. In certain aspects of the present invention, the antistatic agent can be glycerol monostearate. The antistatic agent can be included in the polymer mixture, and its amount, based on the total weight of the polymer mixture, is at least the following, equal to the following and / or between any two of the following values: 0.01wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt% and 1wt%.

[0063] Lubricants can be added to the polymer mixture to improve the mold making properties. The lubricant can be a low molecular weight compound in a macromolecular compound such as a fatty acid, a fatty acid ester, a wax ester, a fatty alcohol ester, an amide wax, a metal carboxylate, a monoalkanoic acid, a monoalkanoic acid ester, or a paraffin or polyethylene wax. In certain aspects of the present invention, the lubricant is a metal stearate. Non-limiting examples of metal stearates include zinc stearate, calcium stearate, lithium stearate, or a combination thereof, preferably calcium stearate. The polymer mixture can include a lubricant in an amount based on the total weight of the polymer mixture, and an amount of at least the following, equal to the following, and / or between any two of the following values: 0.01wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt% and 1wt%.

[0064] Antioxidants and / or heat stabilizers can prevent polymer degradation during processing. Phosphites are known thermal oxidation stabilizers for polymers and other organic materials. Antioxidants can be phosphite-based antioxidants. In some aspects, phosphorous acid antioxidants include but are not limited to triphenyl phosphite, diphenyl alkyl phosphites, phenyl dialkyl phosphites, trinonyl phosphites, tridodecyl phosphites, trioctadecyl phosphites, pentaerythritol diphosphite distearyl esters, tris (2,4-di-tert-butylphenyl) phosphites, diisodecyl pentaerythritol diphosphites, bis (2,4-di-tert-butylphenyl) pentaerythritol diphosphites tristearyl sorbitol triphosphites, and tetrakis (2,4-di-tert-butylphenyl) -4,4'-biphenyl diphosphites, bis (2,4-di-sec-butylphenyl) pentaerythritol diphosphites. The polymer mixture may include an antioxidant in an amount of at least, equal to, and / or between any two of the following values, based on the total weight of the polymer mixture: 0.1 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.8 wt%, 0.9 wt%, and 0.1 wt%. Non-limiting examples of commercially available antioxidants or heat stabilizers include Irganox 1010 and Irgaphos-168 (both available from BASF), or Doverphos S9228T from Dover Chemical Company.

[0065] Nucleating agents can also be used in polymer mixtures. Nucleating agents can be considered as additives added to polymers to promote crystal growth in polymer melts. One or more nucleating agents can be used. Such nucleating agents may include, but are not limited to, cyclic dicarboxylates and talc. Talc is generally used as a filler when used in larger amounts. When used in lower amounts (i.e., less than 5wt%), talc can be used as a nucleating agent. The combined use of a cyclic dicarboxylate first nucleating agent and a talc second nucleating agent has been described in U.S. Pat. No. 11,136,446, which is now incorporated herein by reference. When using this combination, the amount of nucleating agent may be different. For example, the weight ratio of cyclic dicarboxylates to talc may be from 1:1200 to 2:1. The amount of cyclic dicarboxylates used may be from 0.0025wt% to 0.1wt% of the total weight of the composition, and the amount of talc nucleating agent used is from 0.1wt% to 5wt%. A suitable commercially available example of a potassium salt of 1,2-cyclohexanedicarboxylate that can be used as a nucleating agent is the potassium salt of Milliken and Company HPN 20E.

[0066] When forming the PBT composition, the various components of the PBT composition (including the main additives described) and any additional optional auxiliary additives can be dry blended. The PBT components can be in the form of granules, powders, flakes or fluff. The materials are mixed in a conventional mixer, where the PBT and the main additives are mixed with any optional additional or auxiliary additives. Optional secondary additives can be added at the end or processing step of producing the polymer mixture. Suitable machines for such mixing are well known to those skilled in the art. Non-limiting examples include mixers, kneaders and extruders. These materials are then fed directly into the feed zone of the extruder. In some cases, processing can be carried out in an extruder and additives can be introduced during processing. Non-limiting examples of suitable extruders include single screw extruders, counter-rotating and co-rotating twin screw extruders, planetary gear extruders, ring extruders or mixers. The process can be carried out at a temperature of 240°C to 300°C.

[0067] In some embodiments, the PBT components, primary additives, and optional auxiliary additives used to produce the PBT polymer blend of the present invention can be melt extruded by the following typical procedure: weigh the required amounts of PBT and additives, then dry mix, and then feed the mixture into the main feeder of a single-screw or twin-screw co-rotating extruder (length / diameter (L / D) ratio of 25:1 or 40:1) to obtain the final composition. During the mixing process, the PBT, additives, or mixtures thereof can be exposed to high temperatures for a sufficient period of time. The mixing temperature can be above the melting point of the polymer. In some aspects, the extrusion process can be carried out at a temperature of 240°C to 300°C. During the production process, primary and secondary additives can be added online before the PBT resin is pelletized. The amount of additives combined with PBT can be adjusted to provide the weight ratios discussed previously.

[0068] The optional secondary additives may be premixed or added separately to the polymer mixture or its different components. For example, the secondary additives of the present invention may be premixed so that a mixture is formed before adding the PBT or the primary additive. During the mixing and / or incorporation of the additives, the mixture may be placed at an elevated temperature for a sufficient period of time. When the optional secondary additives are added to the polymer resin, the above components may be mixed using methods commonly used in process technology. The mixing temperature may be higher than the melting point of the PBT polymer. In some aspects, the process may be carried out at a temperature of 240°C to 270°C. This "melt mixing" or "melt blending" allows the optional additives of the present invention to be evenly dispersed in the PBT and / or primary additives.

[0069] Articles made from the PBT composition prepared as described above can be used in radio wave applications at 6 GHz or higher frequencies. In particular, the Dk value of the PBT and / or articles formed therefrom may be 3.1, 3.0, 2.9, 2.8, 2.7, 2.6, 2.5, 2.4, 2.3, 2.2, 2.1 or 2.0 or less when measured at 6 GHz or higher frequencies. The Df value of the PBT and / or articles formed therefrom may also be 0.005, 0.004, 0.003, 0.002, 0.001, 0.0005 or less when measured at 6 GHz or higher frequencies.

[0070] In addition, the metal adhesion peel strength of the PBT composition and / or the article formed therefrom can reach 0.1 N / mm, 0.2 N / mm, 0.3 N / mm, 0.4 N / mm, 0.5 N / mm or higher, as measured according to ASTM B533 or IPC-TM-650. The CTE value of the PBT composition or the article formed therefrom can reach 35 ppm / °C, 30 ppm / °C, 25 ppm / °C, 20 ppm / °C, 15 ppm / °C, 10 ppm / °C, 5 ppm / °C or lower, as measured according to ASTM D696. In addition, the HDT of the PBT composition and / or the article formed therefrom at 1.8 MPa can reach 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C or higher, as measured according to ASTM D648.

[0071] The water absorption of the PBT composition or article may also be 0.05 wt%, 0.04 wt%, 0.03 wt%, 0.02 wt%, 0.01 wt% or less as measured according to ASTM D570. 4000MPa, 4100MPa, 4200MPa, 4300MPa, 4400MPa, 4500MPa, 4600MPa, 4700MPa, 4800MPa, 4900MPa, 4900 MPa, 5000 MPa, 5100 MPa, 5200 MPa, 5300 MPa, 5400 MPa, 5500 MPa, 5600 MPa, 5700 MPa, 5800 MPa, 5900 MPa, 6000 MPa, 6100 MPa, 6200 MPa, 6300 MPa, 6400 MPa, 6500 MPa, 6600 MPa, 6700 MPa, 6800 MPa, 6900 MPa, 6900 MPa, 7000 MPa, 7100 MPa, 7200 MPa, 7300 MPa, 7400 MPa, 7500 MPa or more, and a tensile modulus according to ASTM A tensile strength of 35 MPa, 40 MPa, 45 MPa, 50 MPa, 55 MPa, 60 MPa, 65 MPa, 70 MPa, 75 MPa, 80 MPa, 85 MPa, 90 MPa, 95 MPa, 100 MPa, 105 MPa, 110 MPa, 115 MPa, 120 MPa or more as measured by D638.

[0072] The density of the PBT composition may be 1.4 g / cc, 1.3 g / cc or less. It may have a UL94 flame retardancy rating of V0@1.5 mm and a thermal conductivity of 0.05 W / mK, 0.1 W / mK, 0.15 W / mK, 0.2 W / mK, 0.25 W / mK, 0.3 W / mK, 0.0.35 W / mK, 0.4 W / mK, 0.45 W / mK, 0.5 W / mK or more, as measured by ASTM C518.

[0073] PBT compositions may be suitable for specific applications where the operating temperature ranges from -40°C to 210°C or higher.

[0074] The compositions of the present disclosure may "comprise," "consist essentially of," or "consist of" particular ingredients, components, compositions, etc. disclosed throughout the specification.

[0075] The PBT composition formed as described above is usually collected in the form of particles, which can be stored for a period of time or used immediately in a molding process. The molding process may include injection molding, blow molding, compression molding, sheet extrusion, film blowing, pipe extrusion, profile extrusion, calendering, thermoforming, rotational molding or a combination thereof. The final molded PBT product can be used for radio wave applications of 6GHz or higher frequencies. For example, telecommunications equipment or components, high-frequency (greater than 6GHz) electrical equipment, high-frequency (greater than 6GHz) multi-generation telecommunications equipment or components, 5G or higher generation telecommunications antennas and terminal equipment or components, telecommunications equipment housings, radar covers, radio frequency (RF) filters, RF connectors, EMI shielding, antenna substrates, waveguide substrates or carriers, antenna substrates in base station antennas, and automotive radar components may be included.

[0076] Although the present invention has been presented in certain forms, it should be clear to those skilled in the art that the present invention is not limited thereto, but may be varied and modified based on experimental data or other optimizations taking into account the overall economics of the process without departing from the scope of the present invention. Therefore, it is appropriate to interpret the appended claims broadly and in accordance with the scope of the present invention.

Claims

1. A polybutylene terephthalate composition for use in radio wave applications at a frequency of 6 GHz or higher, the composition comprising polybutylene terephthalate, hollow glass bubbles having an average diameter of 5 to 80 microns, and at least one of glass fibers having a length of 0.5 to 10 mm and a width or diameter of 5 to 15 microns, alumina fibers having a length of 1 to 5 mm and a width or diameter of 1 to 30 microns, polyethylene terephthalate, and polycarbonate.

2. The composition according to claim 1, wherein: The composition includes hollow glass bubbles in an amount of 1 wt % to 35 wt %.

3. The composition according to any one of claims 1 and 2, wherein: The hollow glass bubble has at least one of the following: The crushing strength measured by QCM is equal to or greater than 30MPa; A true density of 0.3 g / cc to 0.8 g / cc as measured by helium pycnometry; and The gas volume ranged from 50% to 90% according to QCM measurements.

4. A composition according to any one of claims 1 to 3, wherein: The composition includes glass fibers in an amount equal to or less than 40 wt % of the total weight of the composition.

5. The composition according to any one of claims 1 to 4, wherein: The glass fiber has a dielectric constant (Dk) equal to or less than 6 when measured at 6 MHz or higher according to ASTM D150; a dissipation factor (Df) equal to or less than 0.005 when measured at 6 MHz or higher according to ASTM D150; and a coefficient of thermal expansion (CTE) equal to or less than 35 x 10 -6 / ℃.

6. A composition according to any one of claims 1 to 5, wherein: The composition includes alumina fibers in an amount equal to or less than 40 wt % of the total weight of the composition.

7. A composition according to any one of claims 1 to 6, wherein: The polybutylene terephthalate is a low intrinsic viscosity (IV) resin having an IV equal to or less than 1.4 dl / g or a high IV resin having an IV equal to or greater than 1.5 dl / g or a mixture of these resins, as measured in dilute solution using a capillary viscometer following the ISO-1628-5 protocol.

8. A composition according to any one of claims 1 to 8, wherein: The composition includes polycarbonate in an amount equal to or less than 30 wt % of the total weight of the composition.

9. The composition according to any one of claims 1 to 8, wherein: The composition includes polyethylene terephthalate in an amount equal to or less than 30 wt % of the total weight of the composition.

10. The composition according to any one of claims 1 to 10, further comprising: At least one of a stabilizer, a coupling agent, a nucleating agent, a thermal conductor, a flame retardant additive, a thermal conductive additive, a binder, an anti-blocking agent, an antistatic agent, an antioxidant, a neutralizer, an acid scavenger, a foaming agent, a crystallization aid, a dye, a flame retardant, a filler, a hard filler, a soft filler, an impact modifier, a release agent, an oil, another polymer, a pigment, a treating agent, a reinforcing agent, a light stabilizer, an anti-UV agent, a slip agent, a flow modifier, and a combination thereof.

11. The composition according to any one of claims 1 to 11, wherein: The polybutylene terephthalate composition has a Dk value equal to or less than 2.5 when at 6 GHz or more and a Df value equal to or less than 0.005 when at 6 GHz or more, and at least one of the following: Metal adhesion peel strength equal to or greater than 0.1 N / mm measured according to ASTM B533 or IPC-TM-650, A coefficient of thermal expansion (CTE) equal to or less than 35 ppm / °C as measured according to ASTM D696; Heat deflection temperature (HDT) equal to or greater than 200°C as measured according to ASTM D648; A water absorption of 0.05 wt% or less as measured in accordance with ASTM D570; A tensile modulus equal to or greater than 2000 MPa as measured according to ASTM D638; A tensile strength equal to or greater than 35 MPa as measured in accordance with ASTM D638; Density below 1.4g / cc; UL94 flame retardancy rating is V0@1.5mm; and Thermal conductivity equal to or greater than 0.3 W / mK as measured according to ASTM C518.

12. The composition according to any one of claims 1 to 12, wherein: The polybutylene terephthalate composition is formed into an article.

13. The composition according to claim 13, wherein: The article includes at least one of telecommunication equipment or components, high frequency (>6GHz) electrical equipment, high frequency (>6GHz) multi-generation telecommunication equipment or components, 5G or higher generation telecommunication equipment or components, telecommunication equipment housing, antenna cover, radio frequency (RF) filter, RF connector, EMI shielding, antenna substrate, waveguide substrate or carrier, antenna substrate in base station antenna, and automotive radar component.

14. A method for molding a polybutylene terephthalate composition for use in 6 GHz or higher frequency radio wave applications, the method comprising modifying the polybutylene terephthalate by: The polybutylene terephthalate is melt-mixed with a hollow glass bubble material having an average diameter of 5 to 80 microns, and at least one of glass fibers having a length of 0.5 to 10 mm and a width or diameter of 5 to 15 microns, alumina fibers having a length of 1 to 5 mm and a width or diameter of 1 to 30 microns, and polycarbonate, so that these materials are dispersed throughout the polybutylene terephthalate.